2009
DOI: 10.1677/joe-09-0086
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a novel secreted peptide, INM02, and regulation of its expression by glucose

Abstract: We report the identification of a novel secreted peptide, INM02.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…Use of those tissues was approved by the Medical Ethics Committee at Huashan Hospital, Fudan University. Northern blotting was performed using a kit (non-isotopic digoxigenin Northern Starter; Roche Diagnostics) as described previously [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of those tissues was approved by the Medical Ethics Committee at Huashan Hospital, Fudan University. Northern blotting was performed using a kit (non-isotopic digoxigenin Northern Starter; Roche Diagnostics) as described previously [29].…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant pET32-GMRP1 vector was transformed into E. coli strain BL21. Recombinant GMRP1 protein was produced and purified, and polyclonal antibody against human GMRP1 generated by immunising rabbits as described previously [29].…”
Section: Methodsmentioning
confidence: 99%
“…We, as well as others, have previously suggested that elevated glucose levels can cause altered gene expression in vascular and islets cells (14)(15)(16)(17) (18). He also reported that these genes were differentially regulated by high (22 mM) compared to low glucose (5.5 mM) concentrations.…”
Section: Introductionmentioning
confidence: 64%
“…Consequently, h HSS1 defines a new class of secreted factors. Although little is known about h HSS1, there is evidence that h HSS1 is one of the glucose-responsive genes with both mRNA and protein secretion being regulated by glucose [ 1 ]. As such, it is speculated that h HSS1 could be associated with the functions of pancreatic islets, specifically beta-cells [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about h HSS1, there is evidence that h HSS1 is one of the glucose-responsive genes with both mRNA and protein secretion being regulated by glucose [ 1 ]. As such, it is speculated that h HSS1 could be associated with the functions of pancreatic islets, specifically beta-cells [ 1 ]. Recently, h HSS1 was identified as endoplasmic reticulum (ER) membrane protein complex subunit 10 (EMC10), one of the components of ER associated degradation (ERAD), an ubiquitin and proteasome dependent process [ 2 ].…”
Section: Introductionmentioning
confidence: 99%